The Plays of Alma de Groen - Perkins, Elizabeth, (Chiasma ;, 1994)
Alma De Groen is a New Zealand born playwright who came to Australia in 1964, married the artist Geoffrey De Groen and began writing plays in 1968. Twenty-four years after the performance of her first play she has made a formidable contribution to contemporary drama with stage plays and with television, film and radio scripts, each of which is distinguished by her unique dramatic vision and her unusual insight to human life and society. Each play is distinct from the others, beginning with her first performed stage play, The Joss Adams Show (1970), through to the controversial and highly acclaimed The Rivers of China (1987), and the compassionate The Girl Who Saw Everything (1991). The importance of her work has been recognised by awards which include two AWGIEs and the New South Wales State Award and the Victorian Premier's Award for Drama in 1988.